Locust Bean Gum: Processing, Properties and Food Applications - Singh, Arun K.; Malviya, Rishabha; Rao, Gudhanti Siva Naga Koteswara (Recent Advances in Food Nutrition & Agriculture, 2022)
Locust bean gum is derived from the seed endosperm of the Ceratonia siliqua carob tree and is known as locust bean or carob gum. Food, medicines, paper, textile, oil drilling, and cosmetic sectors all use it as an ingredient. Hydrogen bonding with water molecules makes locust bean gum useful in industrial settings. In addition, its dietary fibre activity helps regulate numerous health issues, including diabetes, bowel motions, heart disease and colon cancer. Locust bean gum production, processing, composition, characteristics, culinary applications, and health advantages are the subject of this article.
Keywords: industrial application